Experimental determination of pyrite and molybdenite oxidation kinetics at nanomolar oxygen concentrations. (15th March 2019) - Johnson, Aleisha C.; Romaniello, Stephen J.; Reinhard, Christopher T.; Gregory, Daniel D.; Garcia-Robledo, Emilio; Revsbech, Niels Peter; Canfield, Donald E.; Lyons, Timothy W.; Anbar, Ariel D.
Abstract: Constraining the rate at which sulfide minerals undergo oxidative weathering at low atmospheric O2 is crucial for understanding the evolution of the Archean and Proterozoic biosphere when O2 was a trace atmospheric gas. However, recent studies attempting to constrain sulfide oxidation rates, atmospheric O2 sinks, and trace metal delivery to seawater under Archean conditions are limited by the need to extrapolate from experimental pyrite oxidation kinetics determined at much higher O2 levels. Extrapolation of those data sets to Archean levels of O2 (<10 −5 present atmospheric level or PAL prior to 2.4 Ga) leads to more than an order of magnitude uncertainty in sulfide mineral oxidation rates, hampering efforts to quantify oxidative weathering under early Earth conditions. To quantify sulfide oxidation kinetics at low p O2, we conducted aqueous pyrite and molybdenite oxidation experiments at ∼2–1200 nM dissolved O2 and pH values 1.83, 5.08, and 8.58. Our experimental approach used LUMOS O2 sensors to extend the p O2 range explored by oxidation experiments down to 10 −5 PAL p O2, the limit of the sensors, which is up to three orders of magnitude lower than the p O2 range explored in previous work. From these experiments, we use 28 independent rate measurements to derive a new rate law for the oxidation of pyrite as a function of p O2 : r pyrite = 10 - 8.83 ( ± 0.27 ) O 2 0.50 ± 0.04 H + - 0.25 ± 0.02, Where r pyrite is the rate of oxidation in mol/m 2 sec, and the activities of dissolved [O2 ] and [H + ] are in (mol/L). Our results most closely match the previous rate law presented by Williamson and Rimstidt (1994), but indicate a stronger pH dependence than previous studies. We also present the first kinetic rate law for molybdenite oxidation at low O2, based on 13 independent rate measurements: r molybdenite = 10 - 8.3 ( ± 2.3 ) O 2 0.5 ± 0.3, Where r molybdenite is the rate of oxidation in mol/m 2 sec, and the activity of dissolved [O2 ] is in (mol/L). We find molybdenite oxidation to be nearly as rapid as pyrite oxidation even at low concentrations of dissolved O2 (equivalent to <10 −5 PAL p O2 ), in contrast to previous work which argued for a threshold effect for molybdenite oxidation. Both pyrite and molybdenite oxidation kinetics exhibit a constant half-order dependence on dissolved O2 down to nanomolar levels of O2 . We show that this behavior is best explained by a reaction mechanism in which O2 undergoes dissociative adsorption to the sulfide mineral surface. This mechanism helps to resolve major uncertainties regarding the reaction mechanism of O2 with pyrite and molybdenite mineral surfaces and provides a strong theoretical basis for the robust extrapolation of present results to higher and lower O2 concentrations.